2020
DOI: 10.1371/journal.pone.0234810
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome of growth restricted fetuses with abnormal umbilical artery Doppler waveforms compared to growth restricted fetuses with normal umbilical artery Doppler waveforms at a tertiary referral hospital in urban Ethiopia

Abstract: Background Intrauterine growth restriction is defined as a fetal weight below the 10th percentile for a given gestational age and can be identified using umbilical artery Doppler velocimetry which is a non-invasive technique. The objective of this study was to determine the perinatal outcome of growth-restricted fetuses with abnormal umbilical artery Doppler study compared to those with normal umbilical artery Doppler waveforms at a tertiary referral hospital in Ethiopia. Methods A prospective cohort study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Mortality was not observed in any group. Tolu LB et al [9] showed 15 neonatal deaths in both the groups. 24% from those having abnormal Doppler scan and 4.5% from normal Doppler scan group.…”
Section: Discussionmentioning
confidence: 93%
“…Mortality was not observed in any group. Tolu LB et al [9] showed 15 neonatal deaths in both the groups. 24% from those having abnormal Doppler scan and 4.5% from normal Doppler scan group.…”
Section: Discussionmentioning
confidence: 93%
“…Abnormal placentation is underlying pathology in pre-eclampsia and in it trophoblastic invasion of spiral arterioles is impaired and inadequate leading to increase resistance in uteroplacental circulation and decrease perfusion [4][5][6] . Preeclampsia is responsible for various adverse outcomes including prematurity, low birth weight, neonatal intensive care, intrauterine foetal death, foetal hypoxia, perinatal death 3 .…”
Section: Introductionmentioning
confidence: 99%
“…These changes in blood flow can be measured by non-invasive method i.e. Doppler ultrasound velocimetry and help to diagnose in-time foetal compromise so that timely intervention can be taken to decrease foetal morbidity and mortality 5,6 . The first application of doppler velocimetry in obstetrics was reported by Fitzgerald et al 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal timing for delivery for IUGR affected pregnancies remains controversial. Sever fetal morbidities and deaths may be prevented by proper antenatal surveillance tests and timed delivery [9] .…”
Section: Introductionmentioning
confidence: 99%